The MapZ-Mediated Methylation of Chemoreceptors Contributes to Pathogenicity of Pseudomonas aeruginosa - Shuo Sheng; Shuo Sheng; Lingyi Xin; Lingyi Xin; Joey Kuok Hoong Yam; Joey Kuok Hoong Yam; Joey Kuok Hoong Yam; May Margarette Salido; May Margarette Salido; May Margarette Salido; Nicole Zi Jia Khong; Qiong Liu; et al. (Frontiers in Microbiology, 2019)
The pathogenic bacterium Pseudomonas aeruginosa is notorious for causing acute and chronic infections in humans. The ability to infect host by P. aeruginosa is dependent on a complex cellular signaling network, which includes a large number of chemosensory signaling pathways that rely on the methyl-accepting chemotaxis proteins (MCPs). We previously found that the second messenger c-di-GMP-binding adaptor MapZ modulates the methylation of an amino acid-detecting MCP by directly interacting with a chemotaxis methyltransferase CheR1. The current study further expands our understanding of the role of MapZ in regulating chemosensory pathways by demonstrating that MapZ suppresses the methylation of multiple MCPs in P. aeruginosa PAO1. The MCPs under the control of MapZ include five MCPs (Aer, CtpH, CptM, PctA, and PctB) for detecting oxygen/energy, inorganic phosphate, malate and amino acids, and three MCPs (PA1251, PA1608, and PA2867) for detecting unknown chemoattractant or chemorepellent. Chemotaxis assays showed that overexpression of MapZ hampered the taxis of P. aeruginosa toward chemoattractants and scratch-wounded human cells. Mouse infection experiments demonstrated that a dysfunction in MapZ regulation had a profound negative impact on the dissemination of P. aeruginosa and resulted in attenuated bacterial virulence. Together, the results imply that by controlling the methylation of various MCPs via the adaptor protein MapZ, c-di-GMP exerts a profound influence on chemotactic responses and bacterial pathogenesis.